2019
DOI: 10.1002/ptr.6470
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin antiproliferative and apoptotic effects: Insights into its clinical impact in various types of cancer

Abstract: Silymarin is a complex extract isolated from the plant Silybum marianum, widely known for its prominent antioxidant and hepatoprotective effects, although increasing evidences have reported extraordinary antiproliferative and apoptotic abilities. As a result, several signaling pathways involved in cell cycle control, cell proliferation, and cell death have been deconvoluted as critical mechanisms. In this regard, cyclin and cyclin‐dependent pathways have been the most studied ones. Following that, apoptotic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 78 publications
(116 reference statements)
0
17
0
1
Order By: Relevance
“…Thus, these studies revealed that autophagy also plays an important role in improving intracellular ROS levels. Accumulating evidences showed as well that oxidative stress was responsible for silibinin-induced death in various types of cancer cells 8,12,33 . Recent studies proved that activation of p53 is a primary pathway via which silibinin improved intracellular ROS levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these studies revealed that autophagy also plays an important role in improving intracellular ROS levels. Accumulating evidences showed as well that oxidative stress was responsible for silibinin-induced death in various types of cancer cells 8,12,33 . Recent studies proved that activation of p53 is a primary pathway via which silibinin improved intracellular ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…1a ). It has been widely used to treat and prevent many types of hepatobiliary disorders including alcoholic liver disease, nonalcoholic fatty liver disease, and mushroom poisoning 12 , 13 . Moreover, silibinin not only exert potent inhibitory effect on various types of cancer cells, such as breast cancer cells, prostate cancer cells, and glioma cells 7 , 14 , 15 , but also sensitizes glioma cells to TMZ, TRAIL or arsenic trioxide treatment and prevents hepatocyte injury induced by chemotherapy agent cisplatin 16 – 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin (Sm) and silibinin (Sb) are investigated to exert strong antineoplastic effects in both in vitro and in vivo models of cancer, including cancers of the prostate, bladder, skin, colon, lung, breast, and kidney [35][36][37][38][39][40][41]. During Sm and Sb treatment, several mechanisms have been applied, such as DNA repair, cell cycle arrest, inhibition of growth and pro-liferation in addition to antiangiogenic effects, and blockage of invasion and metastasis [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Previous studies reported that it possess anticancer potential against several cancers like lungs, prostate, breast, cervical, skin, gastric, bladder, leukemia, larynx, nasopharyngeal" hepatic, glioblastoma and malignant melanoma. [12] It interferes with the apoptotic proteins and expression of cell cycle regulators. Silybin and silymarin also regulate the rate of cell survival and apoptosis.…”
Section: Introductionmentioning
confidence: 99%